Acute mediastinitis after gastric rupture due to blunt trauma: A case report. (August 2020) - Noh, Dongsub; Park, Chan Ik; Kim, Jae Hun
Abstract: Acute mediastinitis after gastric rupture due to blunt trauma is very rare. In such cases, the esophageal hiatus widens due to elevated intra-abdominal pressure, and spillage of gastric contents causes acute posterior mediastinitis. The present report describes the case of a 30-year-old man who injured his left flank, which resulted in gastric rupture. During emergency laparotomy, a ruptured stomach was observed and the abdominal cavity and posterior mediastinum were found to be filled with gastric contents. Following partial gastrectomy, multiple loculated fluids were detected around the esophagus. Irrigation and drainage around the esophagus were performed via video-assisted thoracic surgery. After surgery, the patient recovered from acute mediastinitis and was discharged without any significant complications. In patients with upper gastric rupture, acute mediastinitis should be suspected, and video-assisted thoracic surgery may be an appropriate treatment strategy in such patients.